TYPES AND FUNCTIONS OF SYNTACTICAL STYLISTIC DEVICES: ELLIPSIS AND INVERSION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: this is complete about types and functions of syntactical stylistic devices: ellipsis and inversion.